2017
DOI: 10.1111/1365-2745.12689
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transgenerational effects in Knautia arvensis in response to plant community diversity

Abstract: 1. Plant species persistence in natural communities requires coping with biotic and abiotic challenges. These challenges also depend on plant community composition and diversity. Over time, biodiversity effects have been shown to be strengthened via increasing species complementarity in mixtures. Little is known, however, whether differences in community diversity and composition induce rapid transgenerational phenotypic adaptive differentiation during community assembly. We expect altered plant-plant and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 127 publications
(179 reference statements)
2
25
1
Order By: Relevance
“…Open circles and dashed line refer to communities of co-selected plants, closed circles and solid line refer to na€ ıve communities. abiotic or biotic conditions have been observed in previous studies (Lipowsky et al 2011;Zuppinger-Dingley et al 2014;Kleynhans et al 2016;Rottstock et al 2017). Here, we demonstrated that changes in the performance of entire plant communities over time depend on a history of co-selection among the plant species of the assembled mixtures.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Open circles and dashed line refer to communities of co-selected plants, closed circles and solid line refer to na€ ıve communities. abiotic or biotic conditions have been observed in previous studies (Lipowsky et al 2011;Zuppinger-Dingley et al 2014;Kleynhans et al 2016;Rottstock et al 2017). Here, we demonstrated that changes in the performance of entire plant communities over time depend on a history of co-selection among the plant species of the assembled mixtures.…”
Section: Discussionsupporting
confidence: 69%
“…; Rottstock et al . ). Here, we demonstrated that changes in the performance of entire plant communities over time depend on a history of co‐selection among the plant species of the assembled mixtures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of such monoculture and mixture types, with different growth 100 performance and plant functional trait variation, thus suggested that community 101 diversity in the field likely acted as a selective environment (Zuppinger-Dingley et al, 102 2014; Rottstock et al, 2017;van Moorsel et al, 2018b). However, direct evidence for 103 a genetic divergence between the different populations in the field experiment is still 104 missing.…”
mentioning
confidence: 99%